DETERMINATION OF INCOME OF SUVENIR TRADERS IN THE THEMATIC PUBLIC MARKET OF UBUD TOURISM - I Putu Cenik Arsana; Putu Krisna Adwitya Sanjaya (Adisam Publisher, 2024)
Markets have a key role in driving the community's economy, not only as a place to sell community products, but also as a source of very meaningful employment for the surrounding community.This research aims to analyze the influence of business capital, length of business, sales volume and number of buyers on the income of souvenir traders at the Ubud Thematic Tourism People's Market. The sample used was 86 souvenir traders at the Ubud Thematic Tourism People's Market. The research uses primary data where data collection is carried out using the accidental sampling method. The analysis technique used is descriptive and inferential analysis, namely Multiple Linear Regression. The results of the analysis show that the variables of business capital, length of business, sales volume and number of buyers simultaneously influence the income of souvenir traders at the Ubud Thematic Tourism People's Market. Partially, business capital, length of business, sales volume and number of buyers have a positive and significant effect on the income of souvenir traders at the Ubud Thematic Tourism People's Market. The dominant variable that influences souvenir traders' income is the sales volume variable.